Keeping Community Stakeholders Informed About the Rationale for Program Changes (editorial) - John Morton (The Advocate, 2015)
An editorial comment: Communication is the key element in much of education. Gathering input and utilizing the information to help educators understand community perceptions is a vehicle that has long been underutilized in schools.